Orientalism and gender: the portrayal of the oriental women in frederick millingen’s wild life among the koords - Mustafa, Gharbi (Humanities Journal of University of Zakho, 2023)
In Orientalism (1979), one of his most prominent works, Edward Said lays out a critique of the West’s framing and perceptions of the East. It reveals how Eastern communities and individuals are being imagined and reconstructed by the authoritative gaze and ideals of Western imperialism. Said explains how Western writings represent the East as an inferior, the Other which, justifies the European Western power over the East. The depiction of the harem as exotic oriental women is a long-familiar trope found in various Orientalist writings. The paper examines the representations of Oriental women in Frederick Millingen’s Wild Life Among the Koords (1870). The theoretical framework draws on the formulation of the travel writer’s representation of Oriental women in the context of Orientalist discourse and feminist criticism. It explores how the Orientalist constitutes himself and his subjectivity through the agency of desire and supremacy. This paper argues that this is not a question of the other, but rather a question of the Western subject’s views to present his visions of himself within foreign landscapes. Moreover, the detailed description of Oriental women and the depiction of Oriental culture establish modes of reorientation where women are discriminated against and sexualized.